The window of locational opportunity-concept - Ron Boschma (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
This article aims to set out a theoretical concept, i.e. the Window of Locational Opportunity concept, which accounts for notions like indeterminacy, human agency and historical accidents when explaining the spatial pattern of newly emerging industries. We will state that their spatial formation does probably not reveal predictable tendencies of necessity and regularity during their initial stage of development, because structures, conditions and capabilities laid down in the past are unlikely to determine their spatial manifestation. Potential impacts of space are considered to be highly unpredictable: latent triggers or incentives providing opportunities and/or challenges are manifold, while the selection environment may operate only very weakly. As a consequence, we will claim that notions of human agency and accidents are necessitated to `explain' the spatial pattern of new industries. Because there is much uncertainty about the site where new industries will emerge, windows of locational opportunity tend to open up in the event of newly emerging industries: this theoretical concept holds the view that the long-term evolution of the spatial system is potentially, but not necessarily unstable.
Keywords: 330